Synthesis and Structures of ansa‐Titanocene Complexes with Diatomic Bridging Units for Overall Water Splitting. Issue 20 (27th March 2013) - Kessler, Monty; Hansen, Sven; Godemann, Christian; Spannenberg, Anke; Beweries, Torsten
Abstract The synthesis of a series of ansa‐titanocene dichlorides [Cp′2TiCl2] (Cp′=bridged η5‐tetramethylcyclopentadienyl) and the corresponding titanocene bis(trimethylsilyl)acetylene complexes [Cp′2Ti(η2‐Me3SiC2SiMe3)] is described. The ethanediyl‐bridged complexes [C2H4(C5Me4)2TiCl2] (2‐Cl2) and [C2H4(C5Me4)2Ti(η2‐Me3SiC2SiMe3)] (2‐btmsa; btmsa=η2‐Me3SiC2SiMe3) can be obtained from the hitherto unknown calcocenophane complex [C2H4(C5Me4)2Ca(THF)2] (1). Furthermore, a heterodiatomic bridging unit containing both, a dimethylsilyl and a methylene group was introduced to yield the ansa‐titanocene dichloride [Me2SiCH2(C5Me4)2TiCl2] (3‐Cl2) and the bis(trimethylsilyl)acetylene complex [Me2SiCH2(C5Me4)2Ti(η2‐Me3SiC2SiMe3)] (3‐btmsa). Besides, tetramethyldisilyl‐ and dimethylsilyl‐bridged metallocene complexes (structural motif 4 and 5, respectively) were prepared. All ansa‐titanocene alkyne complexes were reacted with stoichiometric amounts of water; the hydrolysis products were isolated as model complexes for the investigation of the elemental steps of overall water splitting. Compounds 1, 2‐btmsa, 2‐(OH)2, 3‐Cl2, 3‐btmsa, 4‐(OH)2, 3‐alkenyl and 5‐alkenyl were characterised by X‐ray diffraction analysis.